2019
DOI: 10.5815/ijem.2019.03.05
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of a Mixed-Mode Domestic Solar Dryer

Abstract: This work focuses on the design and development of a mixed-mode domestic solar dryer in which the slices of pepper, okra and yam were dried simultaneously by both direct radiation through the transparent glass roof of the drying chamber and by the heated air from the solar collector. The dryer was made up of the solar collector, the desiccant chamber and the drying chamber which contains a rack of three trays. The air comes in through the air inlet and heated up within the solar collector and then channeled th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…, 2023b; Saleh and Badran, 2009; Singh et al. , 2006; Ugwuoke et al. , 2019) but none of them got the acceptance among household users.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…, 2023b; Saleh and Badran, 2009; Singh et al. , 2006; Ugwuoke et al. , 2019) but none of them got the acceptance among household users.…”
Section: Introductionmentioning
confidence: 97%
“…The household sector is responsible for about 61% of global food loss and wastage followed by service and retail sectors (UNEP, 2021). In the past few years, several developments have been made in the field of solar drying (Dubey et al, 2022;Eltawil et al, 2012;Eustache, 2017;Ezekoye and Enebe, 2006;Haque et al, 2018;Kaur et al, 2023;Kumar et al, 2023b;Saleh and Badran, 2009;Singh et al, 2006;Ugwuoke et al, 2019) but none of them got the acceptance among household users. The lower thermal performance, higher heat losses, larger drying time and the obvious intermittent operating behavior are some of the limitations of the solar dryers developed for domestic and small-scale applications (Manchanda et al, 2019;Shimpy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that the higher values of drying temperature and time would result in lower quality product. Ugwuoke et al 19 developed and tested a mixed mode domestic solar dryer for the drying of pepper, okra and yam slices. The maximum dryer temperature was reported to be 55°C, 56°C, and 47°C for the drying of pepper (80 g), okra (190 g), and yam slices (310 g), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The inclination angle of solar collector (β) from the horizontal surface was found by using the following formula as calculated by Ugwuoke et al (2019).…”
Section: Solar Collector Designmentioning
confidence: 99%